O sistema de informação/arquivo da Faculdade de Ciências da Nutrição e Alimentação da Universidade do Porto: estudo e implementação de um modelo de gestão da informação - Luísa Cristiana Araújo Ferreira (2018)
The Information Age presents many challenges, namely those resulting from the technology dependence and evolution. Therefore, it is necessary that institutions and other organizations develop integrated information management solutions that optimize their operations, to efficiently and effectively accomplish the respective Mission, bearing in mind that technology is only a means and not an end by itself. This dissertation systematizes the work carried out within a project in an institutional context - the Faculty of Nutrition and Food Sciences of the University of Porto (FCNAUP) - which sought to contribute to the implementation of an integrated information management (IM) model, prioritizing the dematerialization and improvement of the correspondence management process and the consequent organic study and mapping of information flows, the optimization of the physical management of documentation, as well as the improvement of the processes related with information organization and representation and storage, retrieval and use. In order to achieve these objectives, and in the informational perspective, it was adopted the Active and Permanent - University Information System Management Model, focused on infocommunicational flow and structuring an IM approach through a set of 6 processes and 11interconnected services. Additionally, we considered the contributions of the Requirements Engineering and the application of the Project Management methodology. The obtained results include an organic-functional study (ISCNAUP/FCNAUP, 1997-2016), a Procedures Manual, with the first version of the description of the mapped information flows, validated by the producing services, some access and information search tools, namely a List of Users and Permissions, a List of Physical Units, a Classification Plan proposal and List of Series, authority control lists (List of Terms and List of Document Types), as well as the Guidelines on the Archive Physical Storage. A proposal for Organic Regulation of the Documentation and Information Service (SDI) is also presented and a contribution to the specification of the Information Management Policy at FCNAUP. The adoption, incorporation and continuous development of these tools in the services day-to-day will contribute to a greater efficiency and effectiveness on the implementation of new computer modules/applications, namely Correspondence Management and Archive Management, as it is the first guarantee for a systemic vision and an integrated approach to the information system management within this organic unit, in the context of the University of Porto institutional / organizational system. Keywords: information management, records management, archives management, MGSIU-AP, FCNAUP, University of Porto.